Learning Motivation and Interest towards English as a Language or Subject among Bachelor in Secondary Education Students of Altavas College - Geraldine S. Hanayon; Anelyn P. Villorente; Mikko Jan D. Lopez, EdD (Web of Journals Publishing, 2023)
The primary purpose of this study was to determine the level of learning motivation and learning interest towards English as a language or subject among BSED students of Altavas College. The researchers collected the data by using an electronic web-based questionnaire through the Google survey tool (Google Forms) using questions modified from learning motivation and learning interest. The survey comprised 2 subsections according to the participant's learning motivation and a question corresponding to each respondent's learning interest. The analysis was perceived using the frequency count, percentage, and mean. Descriptive analyses were computed. The result showed that on the level of learning motivation, the respondents were "moderately motivated." This signifies that the respondents has a moderate desire towards English as their language or subject. The level of learning interest of Bachelor in Secondary Education of Altavas College was described as "highly interested." It indicates that the respondents are much willing to learn English as their language or subject.
Keywords: Learning motivation, Learning interest